Nationwide Study on Treatment of Mycotic Thoracic Aortic Aneurysms. (February 2019) - Sörelius, Karl; Wanhainen, Anders; Wahlgren, Carl-Magnus; Langenskiöld, Marcus; Roos, Håkan; Resch, Timothy; Vaccarino, Roberta; Arvidsson, Bengt; Gillgren, Peter; Bilos, Linda; Pirouzram, Artai; Holsti, Mari; et al.
Abstract : Objective: Mycotic aortic aneurysms are rare, life threatening, and complex. This nationwide study aimed to assess outcome after repair of mycotic thoracic aortic aneurysms (MTAAs). Methods: Patients treated in Sweden for MTAAs between 2000 and 2016 were identified in the Swedish vascular registry (2010–16) and local patient registries (2000–09). Primary outcome was survival, and secondary outcomes included surgical strategy, rate of infection related complications (IRC), and re-operations. Results: Fifty-two patients (median age 71 ± 8.1 years; 28 [54%] men, 13 [25%] ruptured) were identified (3.6% of all thoracic aortic aneurysm repairs in Sweden). Aneurysm location was aortic arch ( n = 6; 11%), descending aorta ( n = 42; 81%), and multiple locations ( n = 4; 8%). Twenty-nine (56%) patients had positive cultures; the most prevalent agent was Staphylococcus aureus ( n = 16; 31%). Operative techniques included thoracic endovascular aortic repair (TEVAR; n = 35 [67%]), fenestrated/branched TEVAR ( n = 8; 15%), hybrid repair ( n = 7; 14%), and open patch repair ( n = 2; 4%). Survival was 92% (95% confidence interval [CI] 88–96) at 30 days, 88% (95% CI 84–93) at three months, 78% (73–84) at one year, and 71% (64–77) at five years. The mean follow up among survivors (> 90 days) was 45 months (range 4–216 months). Antibiotics were administered for a median of 15 weeks (range 0–220 weeks). IRCs occurred in nine patients (17%): sepsis ( n = 3), graft infection ( n = 3), recurrent mycotic aneurysm ( n = 1), aorto-oesophageal/bronchial fistula ( n = 2). Six (67%) IRCs were fatal; 80% occurred within the first year. Re-operations were performed in nine patients (17%). Conclusions: TEVAR was often used as treatment for MTAAs, with acceptable short- and long-term survival when compared with open cohorts in the literature. IRCs are of concern and warrant follow up and long-term antibiotic treatment.